Circuito Liberdade: análise de dados em redes sociais como instrumento de percepção para a ressignificação dos espaços culturais - Adriana Gonçalves de Oliveira Silva (2018)
This work presents the digital communication focused on the analysis of data in social networks as an actor of great importance for the promotion of the Patrimony. Its multiple applications are accessible to public agencies through paid, free and widely available tools available in the national market or in social networks. The combination of these analyzes brings real-time answers to the institutions, allowing an approximation with the society. Our object of study, the Circuito Liberdade, is an appropriate reference to this interpretative analysis because of its historical and social relevance. The use of one or more data analysis tools associated with the interpretation of metrics allows important considerations about public perception in the symbolic resignification of this space. The temporal analysis carried out in this research reaffirms the importance of digital communication in the public environment and the feasibility of the application of data analysis in social networks as a dynamic and current tool. The data found allow us to understand the positives and negatives of this process of re-signification and to identify factors that contribute to the fragmentation of this space in the perception of the public.